Clustering in Chemical Characteristics and Contaminant Metal Levels of Indonesian Sago Starch: A Comprehensive Analysis of Purity and Quality - Agus Budiyanto; Muhammad Romli; Elisa Anggraeni; Edi I. Wiloso; Mulyana Hadipernata (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Indonesia has the most sago plantations in the world, which means that sago can be used for a wide range of things, including food, animal feed, fuel, fiber, and fertilizer. However, Indonesian sago starch can’t be used more widely in either domestic or international markets because there isn’t enough information about its chemical composition and contaminant levels. This study examines the chemical composition and heavy metal levels of sago starch from various regions of Indonesia. The results show that the chemical properties of sago starch vary from province to province. For example, the carbohydrate content ranges from 84.26% to 94.93%, while the fat and protein content are relatively low. There are also reports of differences in the amounts of amylose and amylopectin. The levels of heavy metals are very low and meet international safety standards, which means that Indonesian sago starch is safe to eat. Sago starch from Indragiri Hilir, Banjarmasin, and Lingga exhibits chemical properties similar to those from Meranti, Indonesia’s primary sago-producing region, suggesting their potential as alternative sources. The appropriate amounts of amylose and amylopectin in these areas make it suitable for food products that require very high flexibility. These results support improving the use of sago starch and help raise the quality and safety standards for Indonesian sago products.